A Novel Approach to Estimate Solution of Volterra Integral Equations - Ahmad, Mumtaz; Tahir, Bushra (Communications in Mathematics and Applications, 2018)
Approximating numerical solution of integral equations is considered to be very important as such equations have number of applications in various fields. In this paper we introduce novel approach to estimate numerical solutions of Volterra integral equations. In the proposed technique, Chebyshev polynomial is employed to approximate solution for an unknown function in the Volterra integral equation. It is observed that the proposed technique is highly suitable for such problems and have very encouraging results. We compare accuracy and efficiency of the method with existing techniques.